1997
DOI: 10.1126/science.277.5325.563
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Vascular and Neural Dysfunction in Diabetic Rats by C-Peptide

Abstract: C-peptide, a cleavage product from the processing of proinsulin to insulin, has been considered to possess little if any biological activity other than its participation in insulin synthesis. Injection of human C-peptide prevented or attenuated vascular and neural (electrophysiological) dysfunction and impaired Na+- and K+-dependent adenosine triphosphate activity in tissues of diabetic rats. Nonpolar amino acids in the midportion of the peptide were required for these biological effects. Synthetic reverse seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
317
5
5

Year Published

1997
1997
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 324 publications
(352 citation statements)
references
References 29 publications
25
317
5
5
Order By: Relevance
“…C-peptide is considered to be a good marker of insulin secretion and has no biological activity of its own. However, over the last decade, several reports have suggested that C-peptide may exert a number of physiological effects, which are probably mediated by stimulation of Na + ,K + -ATPase and endothelial nitric oxide synthetase activities in several tissues [23]. In the early stage of type 1 diabetes, C-peptide replacement results in diminished UAE rate and ameliorates nerve dysfunction [24].…”
Section: Discussionmentioning
confidence: 99%
“…C-peptide is considered to be a good marker of insulin secretion and has no biological activity of its own. However, over the last decade, several reports have suggested that C-peptide may exert a number of physiological effects, which are probably mediated by stimulation of Na + ,K + -ATPase and endothelial nitric oxide synthetase activities in several tissues [23]. In the early stage of type 1 diabetes, C-peptide replacement results in diminished UAE rate and ameliorates nerve dysfunction [24].…”
Section: Discussionmentioning
confidence: 99%
“…*p<0.05 vs control. A representative western blot image is shown in the upper panel of each graph Na + , K + -ATPase by this fragment [6,15,31,32], whereas scrambled C-peptide had no effect. In contrast to a previous study involving mouse endothelial cells [27], we did not observe an increase in p38 MAP kinase phosphorylation, which may be related to tissue-and speciesspecific differences.…”
Section: Discussionmentioning
confidence: 99%
“…No specific C-peptide receptor has been identified [7]. The introduction of a sensitive method, fluorescent correlation spectroscopy (FCS), has allowed specific C-peptide binding to human cells to be detected but the structure of the receptor is still not known.…”
mentioning
confidence: 99%